Artificial intelligence in power system optimization - Ongsakul, Weerakorn; Vo, Dieu Ngoc (Boca Raton : Taylor & Francis, 2013)
'With the considerable increase of AI applications, AI is being increasingly used to solve optimization problems in engineering. In the past two decades, the applications of artificial intelligence in power systems have attracted much research. This book covers the current level of applications of artificial intelligence to the optimization problems in power systems. This book serves as a textbook for graduate students in electric power system management and is also be useful for those who are interested in using artificial intelligence in power system optimization'--
Includes bibliographical references and index.
Keywords: Electric power systems -- Automatic control; Intelligent control systems